2010
DOI: 10.1007/s00432-010-0916-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Wnt antagonist DKK3 is frequently suppressed in sporadic epithelial ovarian cancer

Abstract: To our best knowledge, this is the first time to demonstrate altered expression of DKK3 in ovarian cancer. The latter could be a relevant mechanism for the activation of the Wnt pathway in the carcinogenesis of ovarian cancer but additional studies are required to elucidate the function of DKK3 silencing in ovarian carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
2
18
1
1
Order By: Relevance
“…However, the biological function of DKK-3 protein in Wnt/β-catenin signaling pathway has not been fully defined [26]. The expression of DKK-3 protein is downregulated in some tumor cell lines and tumor tissues including liver, renal, breast, non-small cell lung, prostate, osteosarcoma, melanoma, cervical, ovarian, brain, endometrial, bladder, colon tumor, and the transcriptional silencing is partly due to the aberrant hypermethylation of the DKK-3 promoter [23,28,[33][34][35][36][37][38][39][40][41][42][43][44]. The DKK-3 protein was found to suppress the migration, invasion and motility of osteosarcoma cells and melanoma [37,38].…”
Section: Introductionmentioning
confidence: 98%
“…However, the biological function of DKK-3 protein in Wnt/β-catenin signaling pathway has not been fully defined [26]. The expression of DKK-3 protein is downregulated in some tumor cell lines and tumor tissues including liver, renal, breast, non-small cell lung, prostate, osteosarcoma, melanoma, cervical, ovarian, brain, endometrial, bladder, colon tumor, and the transcriptional silencing is partly due to the aberrant hypermethylation of the DKK-3 promoter [23,28,[33][34][35][36][37][38][39][40][41][42][43][44]. The DKK-3 protein was found to suppress the migration, invasion and motility of osteosarcoma cells and melanoma [37,38].…”
Section: Introductionmentioning
confidence: 98%
“…Another member of the DKK family and a secreted protein, Dickkopf homolog 3 (DKK3), detected in serum using immunosorbent assay is been suggested as a molecular marker for few gynecological cancers including ovarian and endometrial cancers (Jiang et al 2010). Further, it was shown that the levels of DKK3 were downregulated in ovarian cancer and correlated to the lymphatic metastasis of the disease (Jiang et al 2010;You et al 2011). Additionally, DKK3 is a putative inhibitor of the Wnt signaling and downregulation of DKK3 in ovarian cancer is speculated as a tumorigenic mechanism activating Wnt signaling (You et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Further, it was shown that the levels of DKK3 were downregulated in ovarian cancer and correlated to the lymphatic metastasis of the disease (Jiang et al 2010;You et al 2011). Additionally, DKK3 is a putative inhibitor of the Wnt signaling and downregulation of DKK3 in ovarian cancer is speculated as a tumorigenic mechanism activating Wnt signaling (You et al 2011). Claudin 11, CLDN11, a member of claudin family, is a modulator of cell proliferation as well as cell migration (Bronstein et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…3 One such change is the loss of the expression of Dickkopf-3 (Dkk-3) that occurs through epigenetic mechanisms, [4][5][6][7] and is observed in most solid tumors. [8][9][10][11][12][13][14] Dkk-3 is a divergent member of the Dickkopf family of secreted Wnt antagonists that inhibit Wnt/β-catenin signaling by binding to LRP5/6 Wnt co-receptors. [15][16][17] The exact function of Dkk-3, however, is not known, since it does not directly bind LRP5/6, 18 and has been reported to inhibit, 19-22 potentiate 23 or have no effect on 14,24 Wnt/β-catenin activity.…”
Section: Introductionmentioning
confidence: 99%